From climate to caribou: How manufactured uncertainty is affecting wildlife management - Julee J. Boan; Jay R. Malcolm; Mallory D. Vanier; Dave L. Euler; Faisal M. Moola (Wildlife Society Bulletin)
ABSTRACT Over the past decade, declines of Canadian populations of boreal caribou (Rangifer tarandus caribou) have received considerable attention from scientists, government agencies, environmental nongovernmental organizations, Indigenous communities, and the forest industry. Boreal caribou (also known as boreal woodland caribou) was listed as a threatened species in Canada when the Species at Risk Act came into force in June 2003. Many boreal caribou populations have been shown to be decreasing, in some cases precipitously, and empirical evidence from adult survival and calf recruitment surveys indicates that the cumulative effect of habitat disturbance, including that which results from industrial development, is a key driver in the decline. Yet, as scientific understanding of the decline has become clearer, and agreement among scientists and governments about habitat management requirements has increased, campaigns of denial have intensified in the public sphere. In this paper, we examine parallels with climate change rhetoric prolific in the 2000s and show that willful ignorance disguised as skepticism has resulted in public uncertainty despite robust scientific evidence. We show how these strategies of manufactured uncertainty used in climate change denial campaigns have seeped into wildlife management debates, with pernicious results. In this case, it has successfully delayed efforts to effectively address the decline of boreal caribou, which is protected under federal, provincial, and territorial legislation, and inhibited meaningful dialogue about socially acceptable conservation solutions. © 2018 The Wildlife Society.